2007
DOI: 10.1103/physrevb.75.125425
|View full text |Cite
|
Sign up to set email alerts
|

Local electronic signatures of impurity states in graphene

Abstract: Defects in graphene are of crucial importance for its electronic and magnetic properties. Here, impurity effects on the electronic structure of surrounding carbon atoms are considered and the distribution of the local densities of states is calculated. As the full range from near field to the asymptotic regime is covered, our results are directly accessible by scanning tunneling microscopy. We also include exchange scattering at magnetic impurities and elucidate how strongly spin-polarized impurity states aris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
234
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(254 citation statements)
references
References 31 publications
20
234
0
Order By: Relevance
“…In combination with a finite bulk gap, this impurity induced cross-talk between surface and bulk causes the observed disruption of the Dirac spectrum by permitting second-order bulk-assisted scattering processes. In fact, the resonance states in a TI are similar to states found in both graphene [13][14][15] and d-wave high-temperature superconductors, 16 two other materials with Dirac-like lowenergy spectra, thus making a strong argument for a unified local response to impurities for all "Dirac" materials, 17 once any topological protection is lost.…”
mentioning
confidence: 72%
“…In combination with a finite bulk gap, this impurity induced cross-talk between surface and bulk causes the observed disruption of the Dirac spectrum by permitting second-order bulk-assisted scattering processes. In fact, the resonance states in a TI are similar to states found in both graphene [13][14][15] and d-wave high-temperature superconductors, 16 two other materials with Dirac-like lowenergy spectra, thus making a strong argument for a unified local response to impurities for all "Dirac" materials, 17 once any topological protection is lost.…”
mentioning
confidence: 72%
“…As shown in the inset of Fig. 4(a), high-energy Landau levels oscillate remarkably in a magnetic field of strength B = 8 T, indicating that the Ag resonant impurities serve as mild disorder and do not broaden Landau levels seriously [6,8,17,33,57,60]. More interestingly, as B increases, the zeroth Landau level gradually starts to appear and play a dominant role; therefore, the central peak (a combination of resonant peak and the zeroth Landau-level peak) gradually moves away from the resonant peak measured under B = 0 T [see Fig.…”
Section: Resultsmentioning
confidence: 98%
“…3(a). The appearance of midgap states in disordered graphene's ADOS, although predicted by a large number of theoretical studies [5][6][7][8][9][10]17,21,25,42,57], has never been clearly demonstrated by other experimental methods. Quantum capacitance measurement of graphene devices can be used to study the overall effect of resonant impurities with different impurity concentrations n i on a large scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides explaining the effect of single molecule detection reported in [13] it is capable of controlling the occupancy of flat impurity bands in graphene near the Dirac point and can give rise to exchange scattering. This earns future attention, as it can result in strongly spin-polarized impurity states [28] and guides a possible pathway [15] to high temperature magnetic order in this material.…”
mentioning
confidence: 99%